O lado interior do vento é nossa voz: seis diálogos sobre a experiência da migração nas Américas - (:unkn) unknown (Universidade Federal do Pampa, 2023)
This experimental project consisted of creating an e-book with six interviews with migrants and refugees located in different parts of the continent. Seeking to constitute a material focused on the narrative of lives, a humanizing approach was applied to elicit a real dialogue and promote a deepening in their stories, guided by the articulation between chronology, historical, social and cultural aspects, as well as details of personal experience. The objective was to contribute to the visibility of their realities, in the understanding that, revealing the paths of some of them, perhaps it will be representing the collective of individuals who go through these same choices. In this way, it was also intended to invite reflection on aspects verified in the experience of the migratory process, such as xenophobia, social exclusion, discrimination of various kinds and even violence. The work involved bibliographical research and a face-to-face and virtual field survey, with contact with professionals and institutions in charge of supporting this type of population, as well as interviews with the protagonists of the book. It is concluded that the project was successful, as it achieved the purpose of developing and offering the public a frank and profound dialogue with these subjects, obtaining from this instance a discourse that reveals the universality of the phenomenon of migration and its roots. In this way, the work leads the reader to understand, based on diverse and impactful individual experiences, the phenomenon of permanent migratory waves that reconfigure social groups.
Keywords: Migração de nações; Refugiados - Narrativas pessoais; Memória autobiográfica; Emigração e imigração; Migration of nations; Refugees - Personal narratives; CNPQ::CIENCIAS SOCIAIS APLICADAS